2020
DOI: 10.1111/jch.13905
|View full text |Cite
|
Sign up to set email alerts
|

Association of pulse pressure, pulse pressure index, and ambulatory arterial stiffness index with kidney function in a cross‐sectional pediatric chronic kidney disease cohort from the CKiD study

Abstract: The morbidity and mortality of adult and pediatric chronic kidney disease (CKD) and end-stage renal disease (ESRD) populations are mainly driven by cardiovascular disease (CVD). Improving CVD outcomes focuses on risk assessment of factors including diastolic blood pressure (DBP), systolic blood pressure (SBP), left ventricular mass index (LVMI), pulse pressure (PP), and pulse pressure index (PPi), which is calculated as PP/SBP. These markers are also proven predictors of CKD progression; however, their role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…CKD is associated with increased risks of all‐cause mortality, cardiovascular disease, and progression to kidney failure 20,21 . In a cross‐sectional pediatric chronic kidney disease cohort from the CKiD study, they found that the pulse pressure was associated with lower eGFR in pediatric CKD patients 22 . A community‐based cohort study included 1426 participants, followed for a median of 4.8 years and found that central pulse pressure is an independent determinant of renal function 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CKD is associated with increased risks of all‐cause mortality, cardiovascular disease, and progression to kidney failure 20,21 . In a cross‐sectional pediatric chronic kidney disease cohort from the CKiD study, they found that the pulse pressure was associated with lower eGFR in pediatric CKD patients 22 . A community‐based cohort study included 1426 participants, followed for a median of 4.8 years and found that central pulse pressure is an independent determinant of renal function 23 .…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 In a cross‐sectional pediatric chronic kidney disease cohort from the CKiD study, they found that the pulse pressure was associated with lower eGFR in pediatric CKD patients. 22 A community‐based cohort study included 1426 participants, followed for a median of 4.8 years and found that central pulse pressure is an independent determinant of renal function. 23 And previous study have demonstrated that high resting heart rate is a potent predictor of renal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the National Institute of Diabetes and Digestive Kidney Diseases registry in the US demonstrated that PP significantly correlated to the decline of GFR levels. (22) Additionally, one related cohort study found that among patients with CKD in stages IV and V, PP more than 80 mmHg constituted a significant predictor for disease progression. (23) PP was identified as a strong independent predictor of rising ambulatory arterial stiffness index.…”
Section: Discussionmentioning
confidence: 99%
“…The AASI was defined as 1 minus the regression slope. Prior research in pediatric CKD indicated that elevated AASI is linked to high BP [ 55 , 56 ].…”
Section: Cardiovascular Risks and Biomarkers In Pediatric Ckdmentioning
confidence: 99%